The Return of Nature : Socialism and Ecology - Foster, John Bellamy (Book collections on Project MUSE., 2020)
"In "The Return of Nature," John Bellamy Foster uncovers a long history of efforts to unite issues of social justice and environmental sustainability that will help us comprehend and counter today's unprecedented planetary emergencies. Beginning with the deaths of Darwin and Marx, Foster moves on through the rise of the ecological age in the 1960s and 1970s, exploring how socialist analysts and materialist scientists ought to develop a dialectical naturalism, rooted in a critique of capitalism"--